ANALISIS GAYA BAHASA SINDIRAN DALAM VIDEO TIKTOK RIAN FAHARDHI - Agus Mulyanto; Andarini Rani Probowati; Ratih Purnamasari (Jurnal Semantik, 2023)
The existence of social media such as TikTok opens up opportunities for people to express themselves freely. This freedom demands creativity in expression, among others by using a sarcastic language style. This study aims to examine the use of satire language style used by Tiktoker Rian Fahardhi in his video using Keraf's Language Style theory. This research uses descriptive research to describe the sarcastic language style used by Rian Fahardhi in TikTok videos. The data collection technique used is the listening method with note taking technique. The data analysis technique used in this research is content analysis technique. The results showed that Rian Fahardhi used 19 satire language styles consisting of 4 irony language styles, 6 cynicism language styles, and 9 sarcasm language styles. Satire is not only used to convey criticism and aspirations, but it can also be implemented for readers and listeners of language in various types of literary works and outside literature. By using satire, readers or listeners can pay attention to the words used more carefully in writing or speech. So that it can increase understanding and appreciation of the beauty of language and can strengthen the message to be conveyed.